Environmental Discourse Exhibits Consistency and Variation across Spatial Scales on Twitter. (13th July 2022) - Chang, Charlotte H; Armsworth, Paul R; Masuda, Yuta J
Abstract: Social media platforms, such as Twitter, are an increasingly important source of information and are forums for discourse within and between interest groups. Research highlights how social media communities have amplified movements such as the Arab Spring, #MeToo, and Black Lives Matter. But environmental digital discourse remains underexplored. In the present article, we apply automated text analysis to 200, 000 Twitter users in several countries following leading environmental nongovernmental organizations. Some issues such as public action to decarbonize society or species conservation were discussed more intensely than agriculture or marine conservation. Our results illustrate where environmental discourse diverges and converges on Twitter across countries, states, and characteristics, such as political ideology. Using the coterminous United States as a case study, we observed that the prominence of issues varies across states and, in some cases, covaries with political ideology across counties. Our findings show paths forward to characterizing environmental priorities across many issues at unprecedented scale and extent.